Infra-low frequency neurofeedback and insomnia as a model of CNS dysregulation - Moore, Paul Terrence (Frontiers in Human Neuroscience, 2022)
The brain may be considered a “self-regulating organism” inasmuch as it can operate independently. In other words, it can modulate its own activity (endogenous neuromodulation) in response to both internal and external stimuli. The “normal” brain can maintain stable functioning despite a wide range of operating circumstances or exigencies. A dysregulated brain manifests itself in manifold ways that may be categorized as disorders of arousal, instabilities, disinhibitions, localized dysfunction and learned, maladaptive behaviors. Allopathic medical therapeutics to date offers pharmaceuticals and/or invasive procedures which do not address underlying problems with dysregulation effectively, as indicated by the marginal improvements associated with these treatments. Exploiting neuroplasticity via endogenous neuromodulation may provide clinically relevant functional improvement to the many persons who suffer with a poorly regulated brain. Biofeedback in general, and neurofeedback in particular, have an established clinical record of affording such improvement. This brief paper will review what is conventionally known of sleep homeostasis and focus on insomnia as a primary manifestation of brain dysregulation, whether as a solitary symptom or as part of a larger syndrome such as post-traumatic stress disorder, PTSD. It will discuss in brief behavioral/mindfulness treatments which have been used to treat neurologic diseases as this is germane to the phenomenology of neurofeedback (NF). It will explore how neurofeedback may work at the subconscious level and the current clinical experience of the effectiveness of this technique in the treatment of insomnia. It will conclude with a case presentation.